Maritime English Language Needs And Practices In The Port Of Bejaia: An Ethnographic Case Study - Belkacem Outemzabet (The Journal of Studies in Language, Culture and Society)
Algeria joined the International Maritime Organisation in 1963 and has ratified all the international maritime conventions. It has also taken official measures in relation to the use of English for maritime communication by Algerian ship crews and port personnel. However, little is known about language practices in general and English language use and needs in particular of the Algerian port regulation staff (port officers, safety officers, radio officers, pilots). The aim of the present paper is to explore language practices and needs of the port regulation staff in the Port of Bejaia. The investigation adopted a case study methodology with non-participant observations and ethnographic interviews as the main instruments for collecting data. Three port officers, two pilots and two radio officers accepted to be interviewed. The findings of the research revealed the co-existence of five languages in the port of Bejaia, each being used for a different purpose and with a different category of interlocutors. English is used in seven main communicative events, in which Algerian maritime officers and pilots interact with foreign seafarers of diverse nationalities and for a variety of topics and purposes. The findings of this research can be used to design an ESP course for Bejaia’s port regulation personnel.